Aplikasi theory of planned behavior terhadap minat beli wisata kuliner di Yogyakarta - Pamungkas, Aditya Putra (Economics, Finance, and Business Review, 2024)
The purpose of this study is to analyze the buying interest of visitors to Kopi Klotok Yogyakarta as a culinary tourism site using the theory of planned behavior. Respondents in this study consisted of 75 people who had visited Klotok Coffee. The data used in this study were obtained from interviews with respondents using a questionnaire as a data collection instrument. The data analysis technique used is Structural Equation Modeling - Partial Least Square (SEM-PLS) using the SmartPLS 3.0 application. The results of the data analysis show that the variables that significantly affect the purchase intention of visitors to Kopi Klotok Yogyakarta are the variables of attitude, subjective norm, and perceived behavioral control in determining the buying interest of Yogyakarta Klotok Coffee. Based on the study’s results, the company must develop and improve performance to attract buying interest from visitors to Yogyakarta Klotok coffee.